PERBUATAN MELAWAN HUKUM AKIBAT PENGUASAAN TANAH WAKAF TANPA HAK (Studi Putusan Nomor 04/Pdt.G/2018/PN-Ktn) - Uswatun Hasanah, Uswatun Hasanah (Milthree Law Journal, 2025)
Waqf land is an immovable object that also has economic value, and must be managed properly by the nazhir (waqf recipient) in accordance with applicable laws and regulations. The aim of this research is to find out how unlawful acts are in disputes over control of waqf land, the consequences of unlawful acts over control of waqf land in the Civil Code, and how judges consider in resolving cases of unlawful acts caused by control of waqf land in decisions. Number 04/Pdt.G/2018/PN Ktn. The method used is a descriptive method in the form of normative juridical, the data used is primary data and secondary data and the data collection used is a literature study in the decision of the Kutacane District Court in decision Number: 04/Pdt.G/2018/PN-Ktn using the method data analysis approach to law. Analysis of the Judge's Decision regarding control of waqf land, which is based on legal facts concluded in the judge's consideration that it is clearly proven that land Certificate No. 02 is waqf land from wakif Sehaddin to Nazhir. The local community headed by Rasimin has also been proven that the Plaintiff is the Substitute Nazhir in the aquo case, therefore the object of the dispute which is currently controlled by Defendant I and Defendant II must be handed over to the Plaintiff as Substitute Nazhir so that the Court sentenced Defendant I and Defendant II who control Certificate Number 02 of the waqf land to hand it over to the Plaintiff after the decision in the aquo case becomes legally binding.